Karl Polanyi’s ‘socialist accounting’ and ‘overview’ in the age of data analytics - Rief, Silvia (New Political Economy, 2022)
Digital capitalism’s information infrastructure is the subject of contentious debates concerning its transformative effects on the political economy and society. A frequent proposition, referring to older arguments of the ‘socialist calculation debate’, is that with big data analytics the pro-market arguments of neoliberal economists such as Hayek or Mises become obsolete. This article critically examines this proposition by drawing on Karl Polanyi’s notion of overview; a core theme in his outlines of a socialist economy and accounting written in the 1920s. In these contributions to the early Austrian socialist calculation debate, Polanyi discusses how to gain knowledge of the economic and social processes in such a way that the economy can be democratically governed according to its socialist aims and purposes. This article highlights the relevance of Polanyi’s work on socialist accounting, along with his later perspectives on technology and on social scientific method, for reflecting upon data- and algorithm-driven economic governance. Polanyi’s critical analysis of abstraction effected through methods of knowing suggests a sceptical stance vis-à-vis current versions of technological ‘solutionism’, which places its faith in data and algorithms as tools for economic and social, or socialist, planning.
Sociology; Economics
Keywords: Karl Polanyi; accounting; data analytics; digital socialism; economic theory; overview; socialist accounting; socialist calculation

Planning laissez-faire: Supranational central banking and structural reforms - Braun, Benjamin; Carlo, Donato Di; Diessner, Sebastian (Zeitschrift für Politikwissenschaft, 2022)
The mandate of the European Central Bank (ECB) does not extend to labor market and social policies at the national level. Why, despite the reputational costs, did the ECB act as a staunch advocate of structural labor market reforms from 1999 through 2015? We discuss this question through the theoretical lens of Karl Polanyi’s The Great Transformation. Although Polanyi has been a key reference point for the debate on the social consequences of European economic and monetary integration, one of his key insights has received surprisingly little attention—that central banks have the power to mitigate the impact of international economic integration on domestic social protection. Polanyi regarded central banks—much like trade unions—as national-level institutions of non-market coordination, acting as a protective buffer against the functional pressures of the fixed-exchange-rate monetary regime that was the international gold standard. By contrast, the ECB, as a supranational central bank, embodies these functional pressures. This helps explain why, rather than protecting existing social structures against the logic of the fixed-exchange-rate monetary regime, the ECB has sought to protect the monetary regime by going out of its way to re-shape labor market institutions at the national level.
Sociology
Keywords: European Central Bank; Europäische Zentralbank; Karl Polanyi; monetary integration; social protection; sozialpolitik; structural reforms; strukturreformen; wirtschafts- und währungsunion

Karl Polanyi and the Paradoxes of the Double Movement - Vail, John (Routledge, 2022)
This book offers a critical reconstruction of the double movement, the central thesis of Karl Polanyi’s The Great Transformation, one of the most influential books of the 20th century. The double movement is the establishment of a free market economy and the subsequent effort by society to ameliorate the destructive effects of the market. In Polanyi’s bold vision, the double movement constituted the hidden gear of social change and historical transformation within capitalism. The book is a forensic examination and critique of Polanyi’s argument. It develops an interpretive framework of the double movement as four interrelated social processes: the establishment of the self-regulating market, the rise of a market society that deepens and extends market imperatives, a social protection phase that constrains the market and safeguards society, and the contradictions and crises that result from this clash of social principles. The book will be an indispensable guide for students and scholars across the social sciences which illuminates the relevance of Polanyi’s insights to a critical understanding of the contemporary era –the scourge of insecurity and inequality, the multiple crises of neoliberalism, the rise of right wing populism- as well as those interested in egalitarian and emancipatory alternatives to capitalism.
Keywords: double movement; market society